Non-parametric statistical models in university-level textbooks (2022)
Currently, statistical inference is a key element to apply the experimental scientific method. However, classic textbooks give a great importance to parametric methods, biasing their use in various academic-research fields. The objective of this research work is focused on the investigation of the treatment given by university texts to the subject of non-parametric statistical models in relation to hypothesis testing. The methodology includes content analysis techniques applied to 10 classic statistics books and 12 specialized in non-parametric statistics. The results showed that the classic statistics books used in different universities careers deal with little content on non-parametric methods and with different levels of depth. It is concluded that university textbooks give low importance to the approach of non-parametric models, required in a diversity of investigative practices.